Psychology of color as a strategy for advertising agencies - Ortiz Barbosa, María Fernanda; Pacheco Sánchez, Carlos Alberto (Universidad Francisco de Paula Santander, 2017)
In advertising agencies, a large number of elements are involved, which generate a sufficiently specific type of benefit in the service. Within this wide scope "Colour" can be highlighted as a key factor from its components and functions that are linked to the psychology of colour, correlated with the importance that this brings. In keeping with this definition, the aim of the research is to identify the value of colour psychology, its influences and essential aspects in advertising services, applying a quantitative approach with a descriptive scope. It was concluded that the components, the relationship of the technology and the criteria of the colours when offering an advertising service requires constant awareness and improvements to increase and improve the product quality.